Dinamika Merger Bank Syariah Indonesia (BSI) dalam Perspektif Kinerja Keuangan: Studi Komparatif dan Analisis - Octavian, Hieta; Ermawati, Wita Juwita; Anggraeni, Lukytawati (Universitas Syiah Kuala, 2025)
The merger of three state-owned Islamic banks into Bank Syariah Indonesia (BSI) represents a strategic effort to enhance the competitiveness and institutional efficiency of the national Islamic banking sector. This study aims to analyze changes in financial performance before and after the merger using the CAMELS framework and to formulate institutional strengthening strategies based on SWOT analysis, supported by the IFE and EFE matrices. Employing a quantitative approach, financial report data from 2017 to 2023 were analyzed using a paired sample t-test, Importance-Performance Analysis (IPA), and strategic mapping. The t-test results show that all CAMELS indicators experienced significant changes, including Capital (t=33.586; Sig=0.000), Earnings (t=28.206; Sig=0.000), and Liquidity (t=75.768; Sig=0.000). The IPA results indicate that indicators such as profitability and management shifted to Quadrant I (high priority and high performance), while asset quality and market sensitivity remain in Quadrant II (high priority but underperforming). Based on the weighting and scoring from IPA and t-test results, the IFE score of 3.77 and the EFE score of 3.25 place BSI in the